Quarantine--and its relation to the spread of infectious diseases - McAninch, O. M. (My University, 1902)
Introduction: Quarantine may be defined as the methods and measures imposed by a government-local-state or national-to prevent the introduction of infectious disease into a country or from one locality to another. The term quarantine may be misleading, being derived from the Italian “quarante”, signifying the period of detention as was used by the first Venetian quarantines. It now indicates the entire routine of inspection, disinfection and detention, without regard to the length of time involved. Some measure for the prevention of the spread of infectious diseases can be traced to the mosaiac law in the early ages. In the thirteenth and fourteenth chapters of Leviticus we find very stringent measures enforced upon the children of Israel, for the purpose of preventing the spread of Leprosy; and in their journey through Egypt we find them resorting to fumigation to guard against the plague. And when the pestilence broke out among them we saw Aaron taking his censer, filling it with aromatic spices and stand with the burning incense between the living and the dead, and the plague was stayed. Thus we see that the belief of pleasant odors to destroy animal effluvia is quite ancient.
Citation: McAninch, O. M. Quarantine--and its relation to the spread of infectious diseases. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Quarantine; Infectious Diseases; Medicine; Theses; Manuscripts (documents)